2019
DOI: 10.1093/mnras/stz2758
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-driven outflows in AGNs: revisiting feedback effects of scattered and reprocessed photons

Abstract: We perform two-dimensional hydrodynamical simulations of slowly rotating accretion flows in the region of 0.01 − 7 pc around a supermassive black holes with M BH = 10 8 M . The accretion flow is irradiated by the photons from the central active galactic nucleus (AGN). In addition to the direct radiation from the AGN, we have also included the "re-radiation", i.e., the locally produced radiation by Thomson scattering, line and bremsstrahlung radiation. Compare to our previous work, we have improved the calculat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 64 publications
5
12
0
Order By: Relevance
“…For the particular case of PG1211+143 it was found that the mass outflow rates of the windsṀ out ∼ 1.6M ⊙ yr −1 was comparable to the Eddington accretion rate, implying a radiatively driven accretion disk wind. Recent 2D hydrodynamical simulations have also considered the re-radiation photons (locally produced radiation by Thompson scattering and Bremsstrahlung radiation), which resulted in a better match with observed properties of the outflows (Mosallanezhad et al 2019).…”
Section: The Origin and Acceleration Mechanisms Of The Ionized Outflowsmentioning
confidence: 99%
“…For the particular case of PG1211+143 it was found that the mass outflow rates of the windsṀ out ∼ 1.6M ⊙ yr −1 was comparable to the Eddington accretion rate, implying a radiatively driven accretion disk wind. Recent 2D hydrodynamical simulations have also considered the re-radiation photons (locally produced radiation by Thompson scattering and Bremsstrahlung radiation), which resulted in a better match with observed properties of the outflows (Mosallanezhad et al 2019).…”
Section: The Origin and Acceleration Mechanisms Of The Ionized Outflowsmentioning
confidence: 99%
“…However, all studies based on radiation pressure so far have not used a realistic prescription of radiation field of the AD. Either the disk has been initially treated as a spherical isotropic point-like source with luminosity L (Mosallanezhad et al 2019), or it was approximated applying azimuthally symmetric integration of luminosity over an extended disk so finally the radiation source is centered again at the origin as a point-like source (Risaliti & Elvis 2010). Both cases yield the radiation field to be proportional to the inverse square of the radial distance (with a factor of cos θ for the matter of anisotropy).…”
Section: Introductionmentioning
confidence: 99%
“…Both the photons from the central AGNs and those locally produced can exert radiation force on the gas (Liu et al 2013;Mosallanezhad et al 2019). The total radiation force includes the radiation force F c r from the center AGNs and the re-radiation force F re z due to the locally produced photons,…”
Section: The Radiation Forcementioning
confidence: 99%
“…They find that the accretion flows properties change significantly due to the re-radiation effect and outflows become stronger consequently. Mosallanezhad et al (2019) improve the calculation of radiation force due to the Thomson scattering of Xray photons and the re-radiation force due to locally process. They find that the mass flux and velocity of the outflows are significantly increased.…”
Section: Introductionmentioning
confidence: 99%